PERLINDUNGAN HUKUM KONSUMEN TERHADAP PENJUAL KUE KERING YANG TIDAK MENCANTUMKAN TANGGAL KADALUWARSA (Lex Jurnalica, 2022)
AbstractIn the current era of globalization, many businesses are developing, home industry is one of them. However, some home industry products do not have an expiration date, as happened to the pastry seller in Jelok Village, even though including the expiration date is very important. This is contrary to UUPK No. 8/1999. The method in this article is a qualitative method with a socio-empirical approach, the data obtained through interviews and documentary studies and then analyzed using a deductive method. Consumer Protection Law is a legal certainty to protect consumers. Many consumer rights must be realized, including the right to obtain correct information from products, such as the inclusion of an expiration date which is sometimes underestimated by manufacturers. Thus, it is necessary to enforce consumer protection laws and the responsibilities of related parties in this regard. Many manufacturers do not include an expiration date due to many factors, but besides that they still prioritize the quality of the ingredients. The home industry business is fully supported for the economic benefit of the villagers, and is even more appreciated because there has never been a problem related to the home industry that runs in Jelok Village itself. If at any time there is a problem related to pastries from the producers, they will be fully responsible for the consumer in accordance with applicable law.Keywords: Consumer Protection, Expiration Date, Producer Responsibility.AbstrakDalam era globalisasi saat ini, banyak bisnis yang berkembang, home industry adalah salah satunya. Kendati demikian, sebagian produk home industry tidak memiliki tanggal kadaluwarsa, seperti yang terjadi pada penjual kue kering di Desa Jelok, padahal menyertakan tanggal kedaluwarsa sangat penting. Hal ini bertentangan dengan UUPK Nomor 8 Tahun 1999. Metode dalam artikel ini adalah metode kualitatif disertai pendekatan sosio empiris, data diperoleh melalui metode wawancara dan studi dokumenter kemudian dianalisis dengan metode deduktif. Hukum Perlindungan Konsumen adalah kepastian hukum untuk melindungi konsumen. Banyak hak konsumen yang harus terealisasikan, termasuk hak mendapatkan informasi yang benar dari produk, seperti pencantuman tanggal kadaluwarsa yang kadang disepelekan oleh produsen. Maka, perlu ditegakkan hukum perlindungan konsumen dan tanggung jawab pihak terkait mengenai hal ini. Banyak produsen yang belum mencantumkan tanggal kadaluwarsa karena banyak faktor, namun disamping itu mereka tetap menomor satukan kualitas bahan. Bisnis home industry didukung penuh demi kemaslahatan ekonomi warga desa, dan lebih diapresiasi lagi karena belum pernah terjadi masalah terkait home industry yang berjalan di Desa Jelok sendiri. Apabila suatu ketika terjadi masalah terkait kue kering dari para produsen, mereka akan bertanggung jawab terhadap konsumen secara penuh sesuai hukum yang berlaku.Kata Kunci: Perlindungan Konsumen, Tanggal Kadaluwarsa, Tanggung Jawab Produsen.